La formación de una política social: el caso del Programa de Renovación Habitacional Popular en la ciudad de México - Duhau, Emilio (El Colegio de México A.C., 1987)
The Program for Renovating Lower-class Housing constitutes the Mexican government's most farreaching response to the housing problem that arose after the earthquakes which occurred in September, 1985. Here that response is described in detail, in terms of the definitions and assumptions drawn up by the goverment, of state agencies and of the social actors participating in its realization as an emergency social program. Through this assessment, the author presents a series of basic data on the program and provides an interpretation of the way in which certain fundamental issues that had to be faced in order to carry out the program were resolved. Finally, he offers several reflections on foreseeable social effects, questioning the viewpoint that the definition of a system of full private ownership for the housing units financed through the program will lead to a process of speculative real estate practices that will run counter to the interests of the families benefitting from it.